2015
DOI: 10.1007/s10900-015-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Energy Drinks Among a Sample of College Students and College Student Athletes

Abstract: To assess energy drink (ED) consumption, potential ED correlates, and ED-related motivations among a sample of college students to determine differences based on athlete status (student athlete vs. non-athlete). Six hundred and ninety-two college students completed surveys at a large private university in the United States. Participants completed a paper based questionnaire assessing ED and ED-related variables. Over thirty-six percent (197 non-athletes, 58 student athletes) of participants reported ED consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Indeed, many of the relationships observed among current study outcomes replicated findings from previous studies that used more traditional survey methods. For example, energy drink users were more likely to be male, 2,5,8,11 employed, 13 have higher AUDIT scores, 3 and they were more likely to engage in various risk behaviors. [2][3][4][5][6][7][8][9][10][11]13,14 In addition, results from the delay discounting tasks replicated results from studies that found that larger monetary rewards are discounted less steeply than smaller rewards 47 and delay discounting of condom-protected sex is steeper when partners are perceived as more desirable and less likely to have an STI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many of the relationships observed among current study outcomes replicated findings from previous studies that used more traditional survey methods. For example, energy drink users were more likely to be male, 2,5,8,11 employed, 13 have higher AUDIT scores, 3 and they were more likely to engage in various risk behaviors. [2][3][4][5][6][7][8][9][10][11]13,14 In addition, results from the delay discounting tasks replicated results from studies that found that larger monetary rewards are discounted less steeply than smaller rewards 47 and delay discounting of condom-protected sex is steeper when partners are perceived as more desirable and less likely to have an STI.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent nationwide data on energy drink consumption are scarce, some researchers estimate that over 18% of young adults consume energy drinks at least weekly, 2 and, among college students, this percentage may be as high as 39%. 3 Emerging evidence points to a relationship between energy drink use and various risk behaviors, including alcohol abuse, 2-10 cigarette smoking, 2,6-9,11-13 illicit drug use, 2,6-9,11-13 nonmedical use of prescription drugs, 5,6,8,11,14 fighting, 8 and sexual risk behavior. 8 One of the primary aims of this study was to replicate and extend these findings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested energy drink consumption by college students is associated with lower sleep quantity and quality as well as next day sleepiness [19]. It has also been suggested that episodic (binge) alcohol use is associated with energy drink consumption among college students [15]. In addition, it has been reported that undergraduates who are attempting to lose weight are more likely to use energy drinks [14].…”
Section: Present Studymentioning
confidence: 99%
“…University students who are trying to control or lose weight are more likely to consume higher amounts of caffeine [25]. Binge alcohol drinking is also associated with the intake of energy drinks and other caffeinated beverages by university students [26].…”
Section: Introductionmentioning
confidence: 99%